Food for thought: nano-selenium in poultry nutrition and health - Surai, Peter F.; Kochish, Ivan I. (Animal health research reviews, 2020)
In recent years, nanoparticles have become a fashionable subject of research due to their sizes, shapes, and unique intrinsic physicochemical properties. In particular for the last 5 years, nano-Se has received tremendous attention in terms of its production, characteristic, and possible application for poultry/animal science and medical sciences. Indeed, Nano-Se is shown to be a potential source of Se for poultry/animal nutrition. However, there is an urgent need to address the questions related to nano-Se absorption, assimilation, and metabolism. It is not clear at present if major biological effects of nano-Se are due to Se-protein synthesis, direct antioxidant/prooxidant effects, or both. It is necessary to understand how metallic nano-Se can be converted into H2Se and further to SeCys to be incorporated into selenoproteins. The aforementioned issues must be resolved before nano-Se finds its way to animal/poultry production as a feed supplement and clearly this subject warrants further investigation.